Modelagem para avaliação do potencial de captura e armazenamento geológico de CO2 em campos de petróleo, camadas de carvão e aquíferos salinos no Brasil - Hoppe, Letícia (2012)
Given the global scenario, in which environmental issues are gaining prominence and priority investment, we have the opportunity to contribute by conducting studies for modeling the deployment of technology to capture and geological storage of CO2 in Brazil (CCS), projects using the Clean Development Mechanism, evaluating the degree of inclusion of the current economy in these projects and verifying possible obstacles and necessary modifications.Capture and Geological Storage of CO2 are aimed at injecting previously established geological formations, the carbon dioxide coming from stationary sources, preventing the gas from being released into the atmosphere. The proposed technology can be realized in three different formations: oil fields deep, coal seams and saline aquifers. Faced these alternatives, a study was conducted of technical and economic feasibility of conducting CCS in Brazil for each of their sports. In injection Oil Fields was selected the Barracuda Field, owned by the Campos Basin, this allied to two different stationary sources: Cement and steel mills. The alternative storage Layers of Coal, was selected from the Pool Carbonífera Charqueadas, having as their source of CO2 in the Triunfo/RS, Petrochemical Company Braskem. For injection in Saline Aquifers, was selected the Rio Bonito Formation in the Paraná Basin, being fueled by emissions from ethanol plants in the state of São Paulo. Through the results of this work, we seek to bring to discussion the importance of implementation of projects with high potential to reduce a large-scale release of Greenhouse Study (GHG), which would minimize the adverse effects of actions anthropogenic in synergy with the Convention of the Climate and ratifying the Kyoto Protocol.